The Government's Priority Strategy on the Implementation of Sustainable Construction in the Likupang Special Economic Zone - Daisy Pangemanan; Don Kabo; Teddy Takaendengan; Rilya Rumbayan (Formosa Journal of Sustainable Research, 2023)
The Indonesian government elaborates the concept of welfare by designing new areas that are created with the aim of accelerating and expanding economic development, to empower the potential of local wisdom by upholding the principles of sustainability, integration and competitiveness. The Likupang Special Economic Zone (SEZ) is one of the government's super priority projects and is the focus of supporting the development of the tourism sector in Indonesia, as stated in Government Regulation of the Republic of Indonesia Number 84 of 2019 concerning the Likupang Special Economic Zone. The government as a regulatory regulator forms a common understanding between the government and service providers, investors and the public. The purpose of this research is to formulate the government's priority strategy in implementing sustainable construction in the development of the Likupang SEZ. This research is a qualitative research using survey methods, interviews and Focus Group Discussion (FGD) using SWOT analysis and determining priority strategies using the McFarlan Grid method. This research produced ten government priority strategies which were determined based on the level of urgency of the strategy. This study concludes that 4 (four) strategies are strategic in nature, the top priority to be carried out immediately, 4 (four) strategies are key performance, that it is important to do but not urgent